Preparation Iraqi Attapulgite Clay Using Wet Sieving Process to Be Suitable for Oil Wells Drilling Fluid (Journal of University of Babylon for Engineering Sciences, 2019)
Wet sieving is one of active separation process for clay mineral. In this work, wet sieving was applied to separate attapulgite clay from quartz for Iraqi formation to make it suitable in drilling fluid preparation. The Influence of wet sieving conditions (stirring speed, stirring time and mesh size) on quality and quantity properties of attapulgite clay were investigated. Three stirring speeds (850, 1300 and 1800 rpm) at three stirring times (5, 15 and 20min.) were tested in wet milling process, in addition to three mesh sizes (20,38 and 75µm) were applied in wet sieving process. XRD and FE-SEM were used for mineralogical and morphological characterizing for attapulgite clay. Rheological properties and yield of clay were tested at fresh and salt water using ofite viscometer. Yield of the process was measured by weight differences of clay before wet sieving and after purification process. The results showed that the stirring speed and stirring time had great action on raising the yield of process, where higher yields of process was obtained at 1800 rpm stirring speed for 20 min. at mesh size 75 µm. the results also showed, the mesh size had Direct proportion with a yield of process, while it had a revers fit with dispersion of attapulgite clay. However, best apparent viscosity (15.83 and12.06 Cp) for fresh and salt water respectively, and higher yield of clay (94.21and 81.71 barrel/ton) for fresh and salt water were gained at sieving with 38 µm mesh size. Final result, the best wet sieving condition were stirring speed1800 rpm for 20 min. at 38 µm mesh size.